2020
DOI: 10.1002/aur.2440
|View full text |Cite
|
Sign up to set email alerts
|

Camouflaging in Autism: Examining Sex‐Based and Compensatory Models in Social Cognition and Communication

Abstract: Camouflaging refers to behavioral adaptations that individuals with autism spectrum disorder (ASD), especially females, use to mask symptoms during social situations. Compensation is a component of camouflaging in which an individual's observed behavior is considerably better than actual ability. The study explored diagnostic, sex‐based, and compensatory differences using the Contextual Assessment of Social Skills (CASS). The sample included 161 youth 10:0‐to‐16:11 years (115 males, 46 females). T‐tests were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 91 publications
2
46
0
Order By: Relevance
“…One line of research, using an existing diagnostic observational measure, has demonstrated that in clinical settings, some autistic individuals are rated as appearing less autistic and more normatively socially skilled than would be expected given their autistic traits and social cognition differences (Corbett et al, 2021;Lai et al, 2017Lai et al, , 2019Livingston, Colvert, et al, 2019;Schuck et al, 2019). However, this approach, based on an observational assessment designed to measure the presence or absence of behaviours for the expressed purpose of an autism diagnostic assessment, is limited in describing the full range of camouflaging behaviours exhibited by autistic people in more naturalistic social environments.…”
mentioning
confidence: 99%
“…One line of research, using an existing diagnostic observational measure, has demonstrated that in clinical settings, some autistic individuals are rated as appearing less autistic and more normatively socially skilled than would be expected given their autistic traits and social cognition differences (Corbett et al, 2021;Lai et al, 2017Lai et al, , 2019Livingston, Colvert, et al, 2019;Schuck et al, 2019). However, this approach, based on an observational assessment designed to measure the presence or absence of behaviours for the expressed purpose of an autism diagnostic assessment, is limited in describing the full range of camouflaging behaviours exhibited by autistic people in more naturalistic social environments.…”
mentioning
confidence: 99%
“…Since the discrepancy approach has been used in scientific research before (e.g. Corbett et al, 2021;Lai et al, 2016;Livingston, Colvert, et al, 2019;Parish-Morris et al, 2017;Ratto et al, 2018;Rynkiewicz et al, 2016;Schuck et al, 2019;Wood-Downie, 2021), it is important that we better understand how this approach measures camouflaging behavior.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the magnitude of neural synchronization with a social partner will: (1) increase during the active interaction compared to the baseline; and (2) correlate with autism symptom severity, caregiver reports of social functioning, and theory of mind skills. In addition, given recent evidence that females with ASD may be more successful than males at masking their social difficulties (Halladay et al, 2015;Corbett et al, 2020), we predicted greater interpersonal neural synchrony in females than males with ASD.…”
Section: Introductionmentioning
confidence: 93%